Issues of implementation of IFRS in activity construction enterprises of Ukraine - Rubtsova О.; Kishchenko, T. (Ways to Improve Construction Efficiency, 2019)
The article reflects the necessity to apply international financial reporting standards at construction enterprises, in connection with the adoption of amendments to the law "On Accounting and Financial Reporting in Ukraine", and considers the benefits of the transformation of reporting according to national standards to international requirements. It also highlights a number of advantages in applying international standards and the difficulties of transitioning to modern accounting requirements.